2024
DOI: 10.3389/fcell.2023.1343653
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP/adenosine dynamics in the brain and its role in health and disease

Eiji Shigetomi,
Kent Sakai,
Schuichi Koizumi

Abstract: Extracellular ATP and adenosine are neuromodulators that regulate numerous neuronal functions in the brain. Neuronal activity and brain insults such as ischemic and traumatic injury upregulate these neuromodulators, which exert their effects by activating purinergic receptors. In addition, extracellular ATP/adenosine signaling plays a pivotal role in the pathogenesis of neurological diseases. Virtually every cell type in the brain contributes to the elevation of ATP/adenosine, and various mechanisms underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…ATP and AMP are neuromodulators that regulate numerous neuronal functions in the brain like neurotransmitter synthesis, release, and uptake . During ischemic stroke, ATP depletion occurs due to impaired energy metabolism, leading to neuronal death and brain damage, while AMP levels fluctuate according to the metabolic state of the neurons. , SERS sensors have shown potential for detecting and quantifying ATP with high sensitivity and specificity, with SERS plasmonic core–satellite assemblies and aptamer-conjugated AuNS@Ag detecting ATP levels with an LOD of 0.5 pM . Other studies have also demonstrated label-free detection of ATP in mouse dopaminergic neurons with Au SERS-driven tapered fiber sensors .…”
Section: Protein Sensing With Sers Immunoassaysmentioning
confidence: 99%
“…ATP and AMP are neuromodulators that regulate numerous neuronal functions in the brain like neurotransmitter synthesis, release, and uptake . During ischemic stroke, ATP depletion occurs due to impaired energy metabolism, leading to neuronal death and brain damage, while AMP levels fluctuate according to the metabolic state of the neurons. , SERS sensors have shown potential for detecting and quantifying ATP with high sensitivity and specificity, with SERS plasmonic core–satellite assemblies and aptamer-conjugated AuNS@Ag detecting ATP levels with an LOD of 0.5 pM . Other studies have also demonstrated label-free detection of ATP in mouse dopaminergic neurons with Au SERS-driven tapered fiber sensors .…”
Section: Protein Sensing With Sers Immunoassaysmentioning
confidence: 99%